(untitled) (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we present an example of piecewise linear systems with infinitely many crossing limit cycles defined in two zones separated by a piecewise linear curve with countable corners. Then we prove that under piecewise linear perturbations, the perturbed system can have infinitely many limit cycles, or exactly ℓ limit cycles for any given nonnegative integer ℓ.